THE EFFECT OF THE NATIONAL ECONOMIC RECOVERY PROGRAM ON MSME PRODUCTIVITY DURING THE COVID-19 PANDEMIC - Khotim Fadhli; Zuni Miftakhur Rohmah (JURNAL MANAJEMEN DAN BISNIS, 2021)
This study aims to analyze the effect of the national economic recovery program (PEN) in Indonesia in an effort to increase productivity for MSME actors due to the Covid-19 pandemic. The economic sector, which has also been affected by the Covid-19 pandemic, has resulted in many MSMEs experiencing a decline in turnover, even going bankrupt. So the government makes programs through the national economic recovery policy (PEN) to overcome the problems faced by MSMEs. This research is a quantitative research, with the population in the study are all MSMEs in the Gudo Manik-Manik Center, Jombang Regency, which then determined a sample of 73 respondents using the slovin formula. The sampling technique used was probability sampling with the random sampling method, because taking all the population, namely MSME Gudo Manik-Manik Center, had the same opportunity to become respondents. Data was taken using a questionnaire. The research analysis used is multiple linear regression using SPSS 26. The results of the study state that, the tax incentive which is an economic recovery program (PEN) has no effect on the productivity of MSMEs during the COVID-19 pandemic at the Manik-Manik Gudo Jombang Center. Meanwhile, loan restructuring, which is an economic recovery program (PEN) has a significant impact on MSME productivity during the Covid-19 pandemic at the Gudo Manik-Manik Center. Simultaneously, tax incentives and loan restructuring, which are part of the economic recovery program (PEN) have a significant influence on the productivity of MSMEs during the Covid-19 pandemic at the Gudo Manik-Manik Center, Jombang.